2016
DOI: 10.1002/jca.21485
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cells collection on spectra optia apheresis system using the continuous mononuclear cell collection protocol: A single center report of 39 procedures

Abstract: Spectra Optia CMNC protocol successfully collected CD34+ cells with yields permitting the harvest of sufficient enriched grafts for autologous transplantation. The CD34+ cell yield prediction was excellent. PBSC collection with CMNC protocol had advantages of high processing rate, low product volume, and acceptable contamination by platelets. J. Clin. Apheresis 32:182-190, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
30
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 13 publications
10
30
2
Order By: Relevance
“…However, no bleeding was observed as a direct result of the decreased platelet count and no transfusion support was required. Indeed, the platelet loss observed in adult patients was similar in magnitude to that previously reported with non‐LVL using the Spectra Optia CMNC protocol by Sanderson et al…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, no bleeding was observed as a direct result of the decreased platelet count and no transfusion support was required. Indeed, the platelet loss observed in adult patients was similar in magnitude to that previously reported with non‐LVL using the Spectra Optia CMNC protocol by Sanderson et al…”
Section: Discussionsupporting
confidence: 87%
“…Here we assessed the processing of larger blood volumes using the new continuous mononuclear cell collection (CMNC) protocol on the Spectra Optia apheresis system (Terumo BCT, USA). While the feasibility and efficiency of stem cell collection using Spectra Optia CMNC has been reported previously, this is the first study on LVL performance in pediatric patients assessing side effects, anticoagulant choice and specialized procedures such as adequate venous access and extracorporeal volume . In addition, CD34+ cell yield predictability, determined using a customized algorithm to estimate the blood processing volume required based on circulating CD34+ count and linear regression variables, was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The results are comparable to published data in adults. Cancelas et al reported a 62% CE2 in healthy adult donors, Sanderson et al reported a CE2 of 48.5% in adult myeloma and lymphoma patients . A direct comparison of MNC and CMNS in adults has been published by Lisenko et al who reported in a retrospective analysis a CE2 of 39% to 50% in 72 patients with malignancies, which was not significantly different from the studied MNC group .…”
Section: Discussionmentioning
confidence: 83%
“…Thus, it would be convenient for both the donors and the transplantation coordinating facilities to know when the collection can be completed so they can arrange transportation, etc. Moreover, although PBSC collection is generally a safe, well tolerated procedure [10], procedure related adverse events still occurs [11] and the length of PBSC collection has been associated with more adverse events and bad donation experience [12,13]. Therefore, it is desirable to have a reliable prediction method in order to avoid unnecessarily prolonged collection for the safety of donors.…”
Section: Introductionmentioning
confidence: 99%